2023
DOI: 10.3389/fpubh.2023.1061572
|View full text |Cite
|
Sign up to set email alerts
|

Oncology nursing on the move: a contemporary issue on Chinese oncology nursing in cancer care

Abstract: Cancers have become the primary cause of death among Chinese residents, seriously affecting their health and life. Oncology nursing is a specialized nursing practice focusing on cancer education, prevention, screening, early detection, and palliative and hospice care. China has made tremendous progress in developing oncology nursing. However, to ensure more individuals can get cancer care, the country’s healthcare system still confronts several problems in oncology nursing that need to be addressed to ensure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 54 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…Our study indicated that nurses in PC and oncology units have more knowledge of PC compared with those working in emergency rooms. The reason for this might be nurses who have been working as staff in PC and oncology units have increased opportunities to care for patients who need PC than nurses who have been working in the emergency room and they become familiar with PC knowledge 19 . Nurses' primary goals in the emergency room are to save patients' lives and treat problems that require immediate attention.…”
Section: Discussionmentioning
confidence: 99%
“…Our study indicated that nurses in PC and oncology units have more knowledge of PC compared with those working in emergency rooms. The reason for this might be nurses who have been working as staff in PC and oncology units have increased opportunities to care for patients who need PC than nurses who have been working in the emergency room and they become familiar with PC knowledge 19 . Nurses' primary goals in the emergency room are to save patients' lives and treat problems that require immediate attention.…”
Section: Discussionmentioning
confidence: 99%